Pengaruh Orientasi Kewirausahaan Dan Inovasi Produk Terhadap Kinerja Usaha Kecil Menengah (Ukm) (Studi Kasus Pada UKM Tenun Di Kecamatan Pringgasela Kabupaten Lombok Timur) - Nova Hari Santhi; Yuniar Affandi (Universitas Hamzanwadi, 2020)
The main objectives of this study are (1) Analyzing the Effect of Entrepreneurship Orientation and Product Innovation on SME Performance Individually (Partial), (2) Analyzing the Effect of Entrepreneurship Orientation and Product Innovation on UKM Performance Together (simultaneous) This research is a type of causality research, which is a causal researcher. The population in this study were all Weaving UKM located in Pringgasela District, which amounted to 110 UKM. The sample in this study used saturated samples, that is, the entire population was sampled. Data collection using questionnaire or questionnaire method. Questionnaire methods or questionnaires were conducted to obtain respondents' responses regarding Entrepreneurship Orientation and Product Innovation and Weaving SME Performance. Data analysis used to test the hypothesis in this study is to use the analysis of Multiple Linear Regression contained in the SPSS program v. 19. The results of the research partially (self) show that the Entrepreneurship Orientation variable, namely t-count t-table or 5,627 1,660, then Ho is rejected and the research hypothesis is accepted, meaning Entrepreneurship Orientation has a positive and significant influence on financial performance in UKM Weaving in the Village Pringgasela. Product Innovation Variables, namely t-count t-table or 5.359 1.660 then Ho is rejected and the research hypothesis is accepted, meaning that Product Innovation has a positive and significant influence on financial performance in UKM Weaving in Pringgasela Village. Hypothesis testing results simultaneously (together), from the results of data processing, it is known that F count is 39.030 and F-table in regression 2 free degrees and residual free degrees 109 and Î± 0.05 are 3.09. F count F table (39,030 3,09), then Ho is rejected, meaning that there is a significant influence variable Entrepreneurship Orientation and Product Innovation together towards the Financial Performance of Weaving SMEs in Pringgasela Village